Peran Guru dalam Mempertahankan Nilai-nilai Religiusitas Siswa Kelas V di MI Nurul Huda Tanjungrejo Kecamatan Tongas Kabupaten Probolinggo - Imro Atus Soliha; Nur Khosiah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
Islamic school (Madrasah Ibtidaiyah) is educational institutions that is identical with lessons that breathe with religious values ​​(specifically Islamic Values). Teachers of Madrasah Ibtidaiyah have a very important role for students of Madrasah Ibtidaiyah in social life, especially caring and maintaining the religious values ​​of their students. This study aims to determine the role of a fifth-grade teacher at MI Nurul Huda Tanjugrejo Village in caring and maintaining religious values ​​for madrasah students in the midst of an increasingly modern era. The researcher used descriptive qualitative method. The role of madrasah Ibtidaiyah teacher in Tanjungrejo village, Tongas Probolinggo is very important because the teacher is the second parent after biological parents. The strategies used by fifth grade teachers in maintaining the religious values ​​of students through good habits in their daily lives, especially in madrasah, exemplifying the application of attitudes and behavior in accordance with Islamic law, collaborating with madrasa residents, collaborating with parents or guardians of students to achieve expectations.